Polar stations as testing platforms for space analogue simulations – Case study for Polish potential - Agata Maria Kołodziejczyk; Marek Lewandowski; Adam Nawrot; Ireneusz Sobota (Arctic, Antarctic, and Alpine Research)
Polar regions are naturally isolated and extreme for life, analogous to conditions observed in space. Existing infrastructure in the Arctic and Antarctica could be used not only to conduct a wide range of physical, geographical, biological, and oceanic studies but also to enable space analogue missions. Commercialization of space as well as plans for colonization of the Moon and Mars initiated a new chapter in development of space technologies toward opening the access for everyone interested. The authors explore existing Polish polar stations as platforms for conducting space analogue research to develop adaptations for extreme environments. The article presents the current state of existing infrastructure in the polar regions, which are unique considering the multiple aspects of future settlement beyond Earth. These include food production, energy supply and storage, smart materials, and new forms of communication. The extensive experience of Polish polar researchers provides a relevant background for crew selection and support in conducting physiological and psychological studies on humans. In conclusion, polar stations can function as simulation laboratories for the new era of space exploration.